Original paperBODY POSTURES AND ASYMMETRIES IN FRONTAL AND TRANSVERSE PLANES IN THE TRUNK AREA IN TABLE TENNIS PLAYERS - Barczyk-Pawelec, K.; Bańkosz, Z.; Derlich, M. (Biology of Sport, 2012)
The aim of this research was to assess the body posture within the trunk area in table tennis players and to estimate the correlations between the specific body posture types, their asymmetries and table tennis practice (training experience). To evaluate body posture the photogrammetric method based on the Moiré phenomenon with equipment by CQ Electronic was applied. Tests of significance of difference and correlation were used to estimate the correlation of the observed asymmetries with the training experience. 40 table tennis players and 43 subjects not practising sports participated in the research. The analysis of the results revealed that table tennis players, unlike non-players, are characterized by kyphotic body posture. It probably results from a specific trunk, head and limb position during table tennis matches. Thus, many asymmetries in frontal and transverse planes were observed in the examined table tennis players. Perhaps table tennis, which is characterized by intensive and one-sided trunk muscle work during its performance, is in favour of creating asymmetries. The majority of subjects did not reveal any statistically significant correlations between the observed body posture types, their asymmetries and training experience. However, it was observed that training experience is significantly related to the considerable asymmetry of the inclination angle of shoulder line (KLB). It may result from the negative influence of very intensive, one-sided work and constant work of the shoulder girdle muscles of the playing limb with negligence of exercises of the second limb.